A high heat-resistant glass fiber reinforced ABS material and its preparation method

By grafting polydopamine on the surface of the glass fiber and combining it with graphene oxide, modifying the composite material and grafting the expanded flame retardant, the problem of poor compatibility between ABS materials and glass fibers is solved, significantly improving the mechanical properties, heat resistance and flame retardant of ABS, and expanding its application range.

CN118909391BActive Publication Date: 2025-03-11TAICANG HUADING PLASTIC CO LTD

Patent Information

Application Number
CN202411412378.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-11
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

After the ABS material is reinforced by glass fiber, the interface compatibility is poor, which limits its effect in improving strength, toughness and thermal deformation temperature, affecting product quality and application range.

Method used

The composite material is formed by grafting polydopamine on the surface of the glass fiber and bonding with graphene oxide, and then modified by triethylenetetramine-polyethylene glycol diglycidyl ether to increase dispersion and compatibility, and grafting an expanded flame retardant on the surface to improve flame retardancy and thermal stability.

Benefits of technology

It significantly improves the interface bonding and compatibility between glass fiber and ABS resin, enhances the mechanical properties, heat resistance and flame retardancy of ABS, improves the comprehensive performance of glass fiber reinforced ABS materials, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a high-heat-resistant glass fiber reinforced ABS material and a preparation method thereof, belonging to the technical field of polymer materials. The material comprises the following raw materials: 60-90 parts of ABS resin, 10-20 parts of modified glass fiber, 1-2 parts of lubricant, 1-3 parts of antioxidant and 0.05-0.1 parts of silane coupling agent. In the technical scheme of the invention, the surface of the glass fiber is grafted with KH550, then combined with graphene oxide, and then modified by triethylenetetramine-polyethylene glycol diglycidyl ether, and an intumescent flame retardant is grafted on the surface to obtain the modified glass fiber, which is finally mixed with ABS resin, lubricant, antioxidant and silane coupling agent, and extruded and granulated after melt blending to obtain the high-heat-resistant glass fiber reinforced ABS material. The modified glass fiber not only enhances the interface compatibility between the glass fiber and ABS, but also improves its mechanical properties, heat resistance and flame retardancy, and overall improves the comprehensive performance of the glass fiber reinforced ABS material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular, relates to a high-heat-resistant glass fiber reinforced ABS material and a preparation method thereof. Background Art

[0002] ABS is a terpolymer composed of three monomers: acrylonitrile, butadiene, and styrene. It has the common properties of the three components and has good comprehensive properties, such as chemical corrosion resistance, processing fluidity, and high surface hardness, heat resistance, toughness, impact resistance, and rigidity. At present, ABS has been widely used to make various machinery, instrument parts, and electrical appliances and instrument housings. However, ABS has a lower heat deformation temperature and lower bending strength, which brings certain difficulties to the processing and post-assembly of products. Glass fiber has the advantages of low density, high strength, good thermoplasticity, chemical corrosion resistance, excellent electrical properties, and good processing performance. Glass fiber reinforced composite materials are composite materials made of polymer as the matrix and glass fiber as the reinforcing material, which combines the properties of polymer and glass fiber. Studies have shown that adding glass fiber materials to ABS resin can appropriately improve the strength and heat deformation temperature of ABS.

[0003] Although the tensile strength, flexural strength, flexural modulus, heat deformation temperature and other properties of ABS are improved after being reinforced with glass fiber, due to the polarity and interface differences between ABS resin and glass fiber, and the lack of physical entanglement and chemical bond connection points between the components, the interface compatibility between them is poor, and the reinforcing effect of glass fiber cannot be fully exerted, resulting in limited improvement in the strength, toughness, heat deformation temperature and other aspects of ABS, affecting the final quality of the product and limiting its scope of application. Summary of the invention

[0004] The purpose of the present invention is to provide a high-heat-resistant glass fiber reinforced ABS material and a preparation method thereof. The surface of the glass fiber is coated with polydopamine and then combined with graphene oxide to obtain a composite material. The glass fiber wrapped with polydopamine can increase the interface bonding force between the glass fiber and the graphene oxide. After combining with the graphene oxide, the thermal stability, heat resistance and mechanical properties of the ABS resin can be improved. The composite material is modified by triethylenetetramine-polyethylene glycol diglycidyl ether to obtain a modified composite material. The triethylenetetramine-polyethylene glycol diglycidyl ether improves the dispersion of the composite material in the ABS resin. The modified glass fiber is obtained by grafting an intumescent flame retardant on the surface of the modified composite material, and the intumescent flame retardant increases the flame retardancy and thermal stability of the modified composite material. The ABS resin, modified glass fiber, lubricant, antioxidant and silane coupling agent are mixed, melt blended and then extruded and granulated to obtain a high heat-resistant glass fiber reinforced ABS material. The modified glass fiber enhances the mechanical properties, heat resistance and flame retardancy of the ABS resin, which improves the comprehensive performance of the glass fiber reinforced ABS material as a whole and expands its application range.

[0005] The technical problem to be solved by the present invention is that although the tensile strength, flexural strength, flexural modulus, heat deformation temperature and other properties of ABS are improved after being reinforced with glass fibers, due to the polarity and interface differences between ABS resin and glass fibers, and the lack of physical entanglement and chemical bond connection points between the components, the interface compatibility between them is poor, and the reinforcing effect of the glass fibers cannot be fully exerted, resulting in limited improvement in the strength, toughness, heat deformation temperature and other aspects of ABS, affecting the final quality of the product and limiting its application range.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A high heat-resistant glass fiber reinforced ABS material, comprising the following raw materials in parts by weight: 60-90 parts of ABS resin, 10-20 parts of modified glass fiber, 1-2 parts of lubricant, 1-3 parts of antioxidant and 0.05-0.1 parts of silane coupling agent;

[0008] The modified glass fiber is prepared by grafting an intumescent flame retardant on the surface of a modified composite material; the modified composite material is prepared by modifying a composite material by triethylenetetramine-polyethylene glycol diglycidyl ether; the composite material is prepared by grafting KH550 on the surface of a glass fiber and then combining it with graphene oxide.

[0009] Further, the modified glass fiber is prepared by the following steps:

[0010] The intumescent flame retardant is dissolved in thionyl chloride, refluxed at 65-75° C. for 4-6 hours, and unreacted thionyl chloride is removed by rotary evaporation to obtain a white powder. The modified composite material and tetrahydrofuran are dispersed in an ultrasonic water bath for 1-2 hours, and then the white powder and tetrahydrofuran are added, reacted under a dry nitrogen atmosphere for 2-4 hours, and finally freeze-dried to obtain a modified glass fiber, wherein the amount ratio of the intumescent flame retardant, thionyl chloride and the modified composite material is 0.8-1.2 g:40-60 mL:0.8-1.2 g.

[0011] In the above reaction process, the intumescent flame retardant has a carboxyl group, and the modified composite material has an amino group. The amino group in the modified composite material can combine with the carboxyl group in the intumescent flame retardant to graft the intumescent flame retardant onto the modified composite material to finally obtain modified glass fiber.

[0012] Furthermore, the intumescent flame retardant is prepared by the following steps:

[0013] A1: 2 g of hexachlorocyclotriphosphazene and 10 g of potassium carbonate were dissolved in 25 mL of tetrahydrofuran to obtain a mixed solution, and then 5.8 g of ethyl p-hydroxybenzoate was dissolved in 100 mL of tetrahydrofuran, and then added to the mixed solution, and kept at room temperature for 24 hours. After the solvent was removed by rotary evaporation, it was recrystallized three times with 100 mL of ethanol at 80° C. to obtain product A;

[0014] A2: Dissolve 1 g of product A in 100 mL of 95% ethanol solution, then add 1 g of sodium hydroxide at 45 °C, stir the mixture for 10 h, filter it, and then dissolve it in 100 mL of deionized water. Then add 12 mol / L concentrated hydrochloric acid and adjust the pH value of the mixture to 1. Filter it and wash it 3 times with 50 mL of deionized water to obtain an intumescent flame retardant.

[0015] Furthermore, the modified composite material is prepared by the following steps:

[0016] The composite material and N, N-dimethylformamide are mixed, and the mixture is ultrasonically treated for 0.5-1.5 hours to form a uniform dispersion, and triethylenetetramine-polyethylene glycol diglycidyl ether is added, and stirred at 75-85°C for 22-24 hours, and then washed with N, N-dimethylformamide and deionized water in sequence, and finally the mixture is vacuum freeze-dried to obtain a modified composite material, wherein the usage ratio of the composite material and triethylenetetramine-polyethylene glycol diglycidyl ether is 0.1-0.2g:0.05-0.1g.

[0017] In the above reaction process, the composite material has epoxy groups, and the two ends of triethylenetetramine-polyethylene glycol diglycidyl ether have amino groups. The amino groups in the middle end of triethylenetetramine-polyethylene glycol diglycidyl ether can be combined with the epoxy groups in the composite material through a ring-opening reaction, and the triethylenetetramine-polyethylene glycol diglycidyl ether is grafted to the surface of the composite material, and finally a modified composite material is obtained.

[0018] Further, the triethylenetetramine-polyethylene glycol diglycidyl ether is prepared by the following steps:

[0019] 0.2 g of triethylenetetramine and 200 mL of N,N-dimethylformamide were mixed, and then the temperature was raised to 65° C., and 0.25 g of polyethylene glycol diglycidyl ether was added, and the mixture was stirred at 65° C. for 4 h to finally obtain triethylenetetramine-polyethylene glycol diglycidyl ether.

[0020] In the above reaction process, polyethylene glycol diglycidyl ether has epoxy groups at both ends, and triethylenetetramine has amino groups at both ends. The amino groups in triethylenetetramine can combine with the epoxy groups in polyethylene glycol diglycidyl ether through a ring-opening reaction, and finally amino-terminated triethylenetetramine-polyethylene glycol diglycidyl ether is obtained.

[0021] Furthermore, the composite material is prepared by the following steps:

[0022] The graphene oxide is mixed with a 95% ethanol solution, stirred for 0.5-1.5h, and then ultrasonically treated for 0.5-1.5h to obtain a suspension, and then the alkali-treated glass fiber is immersed in the suspension for 15-20min, and dried to obtain a mixture, deionized water and anhydrous ethanol are mixed, KH550 is added and stirred evenly to obtain a KH550 solution, and the mixture and the KH550 solution are mixed in a hydrochloric acid solution for 25-35min. After the reaction is completed, it is filtered, washed with deionized water, and dried at room temperature to finally obtain a composite material, wherein the amount ratio of the graphene oxide, the ethanol solution, the alkali-treated glass fiber and the KH550 is 0.7-0.8g:90-110mL:4.5-5.5g:0.8-1.2g.

[0023] In the above reaction process, graphene oxide has carboxyl groups, alkali-treated glass fibers have hydroxyl groups, and KH550 has silanol and amine groups after hydrolysis. The silanol groups on KH550 can combine with the hydroxyl groups on the glass fibers, and the amine groups on KH550 can combine with the carboxyl groups on the graphene oxide. The glass fibers and graphene oxide are combined together through KH550 to finally obtain a composite material.

[0024] Furthermore, the alkali-treated glass fiber is specifically processed as follows:

[0025] The glass fiber was heated at 400°C for 30 minutes to remove the sizing agent, and after cooling, it was washed in acetone, and then NaOH solution was added and soaked for 40 minutes to hydroxylate the surface of the glass fiber, and then washed with ionized water for 3 times, and finally dried to obtain alkali-treated glass fiber.

[0026] Furthermore, the glass fiber is alkali-free short glass fiber with a fiber diameter of 10-15 μm and a fiber length of 1-5 mm.

[0027] A method for preparing a high heat-resistant glass fiber reinforced ABS material comprises the following steps:

[0028] The ABS resin, modified glass fiber, lubricant, antioxidant and silane coupling agent are mixed at room temperature for 5-10 minutes, and after being evenly mixed, they are added into a twin-screw extruder, and extruded into granules after melt blending. The extrusion granulation temperature is 205-230°C, and the screw speed is 240-300r / min, and finally a high heat-resistant glass fiber reinforced ABS material is obtained.

[0029] Furthermore, the ABS resin has a melt flow rate of 30-60 g / 10 min at 220° C. / 10 kg.

[0030] Furthermore, the antioxidant is one or more of pentaerythritol ester, phosphite, and n-octadecyl propionate.

[0031] Furthermore, the lubricant is polyethylene wax or N,N'-ethylenebisoleamide.

[0032] Furthermore, the silane coupling agent is vinyl tris(β-methoxyethoxy)silane or vinyl trimethoxysilane.

[0033] Beneficial effects of the present invention:

[0034] (1) In the technical solution of the present invention, the surface of the glass fiber is grafted with KH550 and then combined with graphene oxide to obtain a composite material. The glass fiber and graphene oxide are combined with KH550 to increase the interface bonding force between the glass fiber and the graphene oxide, thereby grafting the graphene oxide onto the glass fiber. The combination of graphene oxide and glass fiber can not only significantly improve the cohesive interaction between ABS and glass fiber, but also effectively enhance the mechanical interlocking between them. By reducing the surface energy and improving the interface adhesion, the reinforcing effect of glass fiber on ABS resin is improved. At the same time, the glass fiber modified with graphene oxide also improves the thermal stability of ABS. and heat resistance, and enhances its mechanical properties such as impact strength, tensile strength, and flexural strength; the composite material is modified by triethylenetetramine-polyethylene glycol diglycidyl ether to obtain a modified composite material, and triethylenetetramine-polyethylene glycol diglycidyl ether is grafted to the surface of the composite material, which can not only prevent the accumulation between the graphene oxide layered structures in the composite material, making it more tightly combined, but also improve the dispersibility of the composite material, increase the compatibility between the composite material and the ABS resin, and also improve the thermal stability of the composite material. At the same time, triethylenetetramine-polyethylene glycol diglycidyl ether also provides amino groups for subsequent grafting reactions, thereby increasing the binding force between the subsequent composite material and the intumescent flame retardant.

[0035] (2) In the technical scheme of the present invention, a modified glass fiber is prepared by grafting an intumescent flame retardant on the surface of a modified composite material. The intumescent flame retardant is grafted onto the surface of the modified composite material, which not only increases the flame retardancy of the modified composite material, but also improves the dispersibility of the modified composite material in ABS resin, further increasing the compatibility between the modified composite material and ABS. The intumescent flame retardant also improves the thermal stability of the modified composite material and enhances the mechanical properties of the ABS resin. After the ABS resin, modified glass fiber, lubricant, antioxidant and silane coupling agent are mixed, added to a twin-screw extruder, extruded and granulated after melt blending, and finally a high heat-resistant glass fiber reinforced ABS material is obtained. The modified glass fiber enhances the mechanical properties, heat resistance and flame retardancy of the ABS resin and improves the reinforcing effect of the glass fiber on ABS.

[0036] (3) In the technical scheme of the present invention, KH550 is grafted onto the surface of glass fiber, and then combined with graphene oxide, modified by triethylenetetramine-polyethylene glycol diglycidyl ether, and then grafted with an intumescent flame retardant to obtain a modified glass fiber. ABS resin, modified glass fiber, lubricant, antioxidant and silane coupling agent are mixed and melt-blended and extruded to granulate to obtain a high heat-resistant glass fiber reinforced ABS material. The modified glass fiber enhances the interface compatibility between the glass fiber and ABS. The prepared high heat-resistant glass fiber reinforced ABS material has good mechanical properties, heat resistance and flame retardant properties, which improves the overall performance of the glass fiber reinforced ABS material and expands its application range. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The glass fibers used in the following examples and comparative examples are alkali-free short glass fibers with a fiber diameter of 13 μm and a fiber length of 3 mm; the melt flow rate of the ABS resin at 220° C. / 10 kg is 45 g / 10 min.

[0039] The specific operation of alkali-treated glass fiber is:

[0040] 1 g of glass fiber was heated at 400°C for 30 min to remove the sizing agent, and after cooling, it was put into 50 mL of acetone for cleaning, and then 20 mL of 1 mol / L NaOH solution was added and soaked for 40 min to hydroxylate the surface of the glass fiber, and then washed three times with 50 mL of deionized water, and finally dried to obtain alkali-treated glass fiber.

[0041] Triethylenetetramine-polyethylene glycol diglycidyl ether is prepared by the following steps:

[0042] 0.2 g of triethylenetetramine and 200 mL of N,N-dimethylformamide were mixed, and then the temperature was raised to 65° C., and 0.25 g of polyethylene glycol diglycidyl ether was added, and the mixture was stirred at 65° C. for 4 h to finally obtain triethylenetetramine-polyethylene glycol diglycidyl ether.

[0043] The intumescent flame retardant is prepared by the following steps:

[0044] A1: 2 g of hexachlorocyclotriphosphazene and 10 g of potassium carbonate were dissolved in 25 mL of tetrahydrofuran to obtain a mixed solution, and then 5.8 g of ethyl p-hydroxybenzoate was dissolved in 100 mL of tetrahydrofuran, and then added to the mixed solution, and kept at room temperature for 24 hours. After the solvent was removed by rotary evaporation, it was recrystallized three times with 100 mL of ethanol at 80° C. to obtain product A;

[0045] A2: Dissolve 1 g of product A in 100 mL of 95% ethanol solution, then add 1 g of sodium hydroxide at 45 °C, stir the mixture for 10 h, filter it, and then dissolve it in 100 mL of deionized water. Then add 12 mol / L concentrated hydrochloric acid and adjust the pH value of the mixture to 1. Filter it and wash it 3 times with 50 mL of deionized water to obtain an intumescent flame retardant.

[0046] Example 1

[0047] The composite material is prepared by the following steps:

[0048] 0.7 g of graphene oxide was mixed with 90 mL of 95% ethanol solution, and stirred at a speed of 1500 r / min for 0.5 h, and then ultrasonically treated for 0.5 h (ultrasonic power of 100 W, oscillation frequency of 40 kHz) to obtain a suspension, and then 4.5 g of alkali-treated glass fiber was immersed in the suspension for 15 min. After drying, a mixture was obtained. 70 mL of deionized water and 30 mL of anhydrous ethanol were mixed, and 0.8 g of KH550 was added and stirred to obtain a KH550 solution. The mixture and the KH550 solution were mixed in 15 mL of a hydrochloric acid solution with a mass concentration of 0.1 mol / L for 25 min. After the reaction was completed, it was filtered, washed with 50 mL of deionized water, and dried at room temperature to finally obtain a composite material.

[0049] Example 2

[0050] The composite material is prepared by the following steps:

[0051] 0.75 g of graphene oxide was mixed with 100 mL of 95% ethanol solution, and stirred at a speed of 1500 r / min for 1 h, and then ultrasonically treated for 1 h (ultrasonic power of 100 W, oscillation frequency of 40 kHz) to obtain a suspension, and then 5 g of alkali-treated glass fiber was immersed in the suspension for 18 min. After drying, a mixture was obtained. 70 mL of deionized water and 30 mL of anhydrous ethanol were mixed, and 1 g of KH550 was added and stirred to obtain a KH550 solution. The mixture and the KH550 solution were mixed in 18 mL of a hydrochloric acid solution with a mass concentration of 0.1 mol / L for 30 min. After the reaction was completed, it was filtered, washed with 50 mL of deionized water, and dried at room temperature to finally obtain a composite material.

[0052] Example 3

[0053] The composite material is prepared by the following steps:

[0054] 0.8 g of graphene oxide was mixed with 110 mL of 95% ethanol solution, and stirred at a speed of 1500 r / min for 1.5 h, and then ultrasonically treated for 1.5 h (ultrasonic power of 100 W, oscillation frequency of 40 kHz) to obtain a suspension, and then 5.5 g of alkali-treated glass fiber was immersed in the suspension for 20 min. After drying, a mixture was obtained. 70 mL of deionized water and 30 mL of anhydrous ethanol were mixed, and 1.2 g of KH550 was added and stirred to obtain a KH550 solution. The mixture and the KH550 solution were mixed in 20 mL of a hydrochloric acid solution with a mass concentration of 0.1 mol / L for 35 min. After the reaction was completed, it was filtered, washed with 50 mL of deionized water, and dried at room temperature to finally obtain a composite material.

[0055] Example 4

[0056] The modified composite material is prepared by the following steps:

[0057] 0.1 g of the composite material prepared in Example 1 was mixed with 80 mL of N, N-dimethylformamide, and the mixture was ultrasonically treated for 0.5 h (the frequency of the ultrasonic treatment was 20 KHz) to form a uniform dispersion, and then 0.05 g of triethylenetetramine-polyethylene glycol diglycidyl ether was added and stirred at 75°C for 22 h. Then, the mixture was washed with 50 mL of N, N-dimethylformamide and 50 mL of deionized water in sequence, and finally the mixture was vacuum freeze-dried (vacuum degree was 13 Pa, freezing temperature was -40°C) to obtain a modified composite material.

[0058] Example 5

[0059] The modified composite material is prepared by the following steps:

[0060] 0.15 g of the composite material prepared in Example 2 was mixed with 100 mL of N, N-dimethylformamide, and the mixture was ultrasonically treated for 1 h (the frequency of ultrasonic treatment was 20 KHz) to form a uniform dispersion, and then 0.08 g of triethylenetetramine-polyethylene glycol diglycidyl ether was added and stirred at 80°C for 23 h. Then, the mixture was washed with 50 mL of N, N-dimethylformamide and 50 mL of deionized water in sequence, and finally the mixture was vacuum freeze-dried (vacuum degree was 13 Pa, freezing temperature was -40°C) to obtain a modified composite material.

[0061] Example 6

[0062] The modified composite material is prepared by the following steps:

[0063] 0.2 g of the composite material prepared in Example 3 was mixed with 120 mL of N, N-dimethylformamide, and the mixture was ultrasonically treated for 1.5 h (the frequency of the ultrasonic treatment was 20 kHz) to form a uniform dispersion, and then 0.1 g of triethylenetetramine-polyethylene glycol diglycidyl ether was added and stirred at 85°C for 24 h. Then, the mixture was washed with 50 mL of N, N-dimethylformamide and 50 mL of deionized water in sequence, and finally the mixture was vacuum freeze-dried (vacuum degree was 13 Pa, freezing temperature was -40°C) to obtain a modified composite material.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 6 is that the composite material prepared in Example 3 is replaced by the alkali-treated glass fiber in Example 3, and the remaining steps and raw materials are the same as Example 6.

[0066] Example 7

[0067] The modified glass fiber is prepared by the following steps:

[0068] 0.8 g of intumescent flame retardant was dissolved in 40 mL of thionyl chloride, refluxed at 65° C. for 4 h, and unreacted thionyl chloride was removed by rotary evaporation to obtain a white powder. 0.8 g of the modified composite material prepared in Example 4 and 40 mL of tetrahydrofuran were dispersed in an ultrasonic water bath for 1 h (the frequency of ultrasonic dispersion was 20 KHz), and then 0.4 g of white powder and 40 mL of tetrahydrofuran were added. After reacting for 2 h in a dry nitrogen atmosphere, the modified glass fiber was finally obtained by freeze drying (the freeze drying temperature was -40° C.).

[0069] Example 8

[0070] The modified glass fiber is prepared by the following steps:

[0071] 1 g of intumescent flame retardant was dissolved in 50 mL of thionyl chloride, refluxed at 70° C. for 5 h, and unreacted thionyl chloride was removed by rotary evaporation to obtain a white powder. 1 g of the modified composite material prepared in Example 5 and 50 mL of tetrahydrofuran were dispersed in an ultrasonic water bath for 1.5 h (the frequency of ultrasonic dispersion was 20 KHz), and then 0.5 g of white powder and 50 mL of tetrahydrofuran were added. After reacting for 3 h in a dry nitrogen atmosphere, the modified glass fiber was finally obtained by freeze drying (the freeze drying temperature was -40° C.).

[0072] Example 9

[0073] The modified glass fiber is prepared by the following steps:

[0074] 1.2 g of intumescent flame retardant was dissolved in 60 mL of thionyl chloride, refluxed at 75° C. for 6 h, and unreacted thionyl chloride was removed by rotary evaporation to obtain a white powder. 1.2 g of the modified composite material prepared in Example 6 and 60 mL of tetrahydrofuran were dispersed in an ultrasonic water bath for 2 h (the frequency of ultrasonic dispersion was 20 KHz), and then 0.6 g of white powder and 60 mL of tetrahydrofuran were added. After reacting for 4 h in a dry nitrogen atmosphere, the modified glass fiber was finally obtained by freeze drying (the freeze drying temperature was -40° C.).

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 9 is that the modified composite material prepared in Example 6 is replaced by the material prepared in Comparative Example 1, and the remaining steps and raw materials are the same as in Example 9.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 9 is that the modified composite material prepared in Example 6 is replaced by the composite material prepared in Example 3, and the remaining steps and raw materials are the same as in Example 9.

[0079] Example 10

[0080] A method for preparing a highly heat-resistant glass fiber reinforced ABS material comprises the following raw materials in parts by weight: 60 parts of ABS resin, 10 parts of modified glass fiber prepared in Example 7, 1 part of polyethylene wax, 1 part of pentaerythritol ester and 0.05 part of vinyl trimethoxy silane.

[0081] The following steps are involved:

[0082] ABS resin, modified glass fiber prepared in Example 7, polyethylene wax, pentaerythritol ester and vinyl trimethoxysilane were mixed at room temperature for 5 minutes, and after being evenly mixed, they were added to a twin-screw extruder, and extruded and granulated after melt blending. The extrusion granulation temperature was 205°C and the screw speed was 240r / min, and finally a high heat-resistant glass fiber reinforced ABS material was obtained.

[0083] Embodiment 11

[0084] A method for preparing a high-heat-resistant glass fiber reinforced ABS material comprises the following raw materials in parts by weight: 80 parts of ABS resin, 15 parts of modified glass fiber prepared in Example 8, 1.5 parts of N,N'-ethylenebisoleamide, 2 parts of phosphite and 0.08 parts of vinyl tris(β-methoxyethoxy)silane.

[0085] The following steps are involved:

[0086] ABS resin, modified glass fiber prepared in Example 8, N,N'-ethylenebisoleamide, phosphite and vinyl tri(β-methoxyethoxy)silane were mixed at room temperature for 8 minutes, and after being evenly mixed, they were added to a twin-screw extruder, and extruded and granulated after melt blending. The extrusion granulation temperature was 220°C and the screw speed was 260r / min, and finally a high heat-resistant glass fiber reinforced ABS material was obtained.

[0087] Example 12

[0088] A method for preparing a high-heat-resistant glass fiber reinforced ABS material comprises the following raw materials in parts by weight: 90 parts of ABS resin, 20 parts of modified glass fiber prepared in Example 9, 2 parts of N,N'-ethylenebisoleamide, 3 parts of n-octadecyl propionate and 0.1 parts of vinyltrimethoxysilane.

[0089] The following steps are involved:

[0090] ABS resin, modified glass fiber prepared in Example 9, N,N'-ethylenebisoleamide, octadecyl propionate and vinyltrimethoxysilane were mixed at room temperature for 10 minutes, and after being evenly mixed, they were added to a twin-screw extruder, and extruded into granules after melt blending. The extrusion granulation temperature was 230°C and the screw speed was 300r / min, and finally a high heat-resistant glass fiber reinforced ABS material was obtained.

[0091] Comparative Example 4

[0092] The difference between this comparative example and Example 12 is that the modified glass fiber prepared in Example 9 is replaced by the material prepared in Comparative Example 2, and the remaining steps and raw materials are the same as Example 12.

[0093] Comparative Example 5

[0094] The difference between this comparative example and Example 12 is that the modified glass fiber prepared in Example 9 is replaced by the material prepared in Comparative Example 3, and the remaining steps and raw materials are the same as Example 12.

[0095] Comparative Example 6

[0096] The difference between this comparative example and Example 12 is that the modified glass fiber prepared in Example 9 is replaced by the modified composite material prepared in Example 6, and the remaining steps and raw materials are the same as Example 12.

[0097] Comparative Example 7

[0098] The difference between this comparative example and Example 12 is that the modified glass fiber prepared in Example 9 is replaced by the alkali-treated glass fiber in Example 3, and the remaining steps and raw materials are the same as Example 12.

[0099] The high heat-resistant glass fiber reinforced ABS materials prepared in Examples 10-12 and Comparative Examples 4-7 are now subjected to performance tests of tensile strength, notched Izod impact strength, flexural strength, heat deformation temperature and flame retardancy. The tensile strength is tested according to GB / T 1040.2-2006, the notched Izod impact strength is tested according to GB / T 1843.2-1996, the flexural strength is tested according to GB / T9341-2000, the heat deformation temperature is tested according to GB / T 1634.2-2004, and the flame retardancy is tested according to the UL94 test standard. The test results are shown in the following table:

[0100] Table 1

[0101]

[0102] It can be seen from the data in Table 1 above that, by comparing Comparative Example 4 with Example 12, it can be seen that the test results of the glass fiber without graphene oxide added to prepare the high heat-resistant glass fiber reinforced ABS material are worse than those of Example 12, indicating that the graphene oxide is grafted onto the glass fiber by KH550, and the graphene oxide can improve the reinforcing effect of the glass fiber on the ABS, improve the cohesive interaction between the ABS and the glass fiber, and further improve the mechanical properties and heat resistance of the ABS;

[0103] From the comparison between Comparative Example 5 and Example 12, it can be seen that the composite material without grafting triethylenetetramine-polyethylene glycol diglycidyl ether is used to prepare the high heat-resistant glass fiber reinforced ABS material, which shows that grafting triethylenetetramine-polyethylene glycol diglycidyl ether to the surface of the composite material can increase the interface compatibility between the composite material and ABS, and further improve the mechanical properties and heat resistance of the glass fiber reinforced ABS material;

[0104] From the comparison between Comparative Example 6 and Example 12, it can be seen that the modified composite material without the grafted intumescent flame retardant is used to prepare the high heat-resistant glass fiber reinforced ABS material, which shows that the grafting of the intumescent flame retardant onto the modified composite material can not only increase the compatibility between the modified composite material and ABS, but also improve the flame retardancy and heat resistance of the glass fiber reinforced ABS material.

[0105] From the comparison between Comparative Example 7 and Example 12, it can be seen that the mechanical properties, heat resistance and flame retardant properties of the high heat-resistant glass fiber reinforced ABS material prepared by using a single glass fiber are worse than those of Example 12, indicating that the modified glass fiber prepared by modifying the glass fiber can better enhance the mechanical properties, heat resistance and flame retardant properties of the ABS resin.

[0106] As can be seen from Table 1 above, the high heat-resistant glass fiber reinforced ABS material prepared in Examples 10-12 is compared with Comparative Examples 4-7. The glass fiber surface is grafted with KH550, and then combined with graphene oxide, modified by triethylenetetramine-polyethylene glycol diglycidyl ether, and then grafted with an intumescent flame retardant to obtain a modified glass fiber, and finally mixed with ABS resin, lubricant, antioxidant and silane coupling agent, and melt blended, extruded and granulated to obtain a high heat-resistant glass fiber reinforced ABS material, which improves the mechanical properties, heat resistance and flame retardancy of the ABS resin as a whole, and meets the test performance requirements. The high heat-resistant glass fiber reinforced ABS material prepared in Comparative Examples 4-7 did not meet the performance requirements. The high heat-resistant glass fiber reinforced ABS material prepared by the present invention not only improves the interface compatibility between glass fiber and ABS, but also has good mechanical properties, heat resistance and flame retardancy, improves the comprehensive performance of the glass fiber reinforced ABS material, and expands its application range.

[0107] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0108] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high heat-resistant glass fiber reinforced ABS material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-90 parts of ABS resin, 10-20 parts of modified glass fiber, 1-2 parts of lubricant, 1-3 parts of antioxidant and 0.05-0.1 parts of silane coupling agent; The modified glass fiber is prepared by grafting an intumescent flame retardant on the surface of a modified composite material; The modified composite material is prepared by modifying the composite material with triethylenetetramine-polyethylene glycol diglycidyl ether; the composite material is prepared by grafting KH550 on the surface of glass fiber and then combining it with graphene oxide; The modified glass fiber is prepared by the following steps: The intumescent flame retardant is dissolved in thionyl chloride, refluxed at 65-75°C for 4-6 hours, and rotary evaporated to obtain a white powder. The modified composite material and tetrahydrofuran are dispersed in an ultrasonic water bath for 1-2 hours, and then the white powder and tetrahydrofuran are added, reacted in a dry nitrogen atmosphere for 2-4 hours, and finally freeze-dried to obtain a modified glass fiber; The intumescent flame retardant is prepared by the following steps: A1: 2 g of hexachlorocyclotriphosphazene and 10 g of potassium carbonate were dissolved in 25 mL of tetrahydrofuran to obtain a mixed solution, and then 5.8 g of ethyl p-hydroxybenzoate was dissolved in 100 mL of tetrahydrofuran, and then added to the mixed solution, and kept at room temperature for 24 hours. After the solvent was removed by rotary evaporation, it was recrystallized three times with 100 mL of ethanol at 80° C. to obtain product A; A2: 1 g of product A was dissolved in 100 mL of 95% ethanol solution, and then 1 g of sodium hydroxide was added at 45 °C, and the mixture was stirred for 10 h. After filtering, it was dissolved in 100 mL of deionized water, and then concentrated hydrochloric acid with a mass concentration of 12 mol / L was added and the pH value of the mixture was adjusted to 1. After filtering and washing with 50 mL of deionized water for 3 times, an intumescent flame retardant was finally obtained; Described triethylenetetramine-polyethylene glycol diglycidyl ether is prepared by following steps: 0.2 g of triethylenetetramine and 200 mL of N,N-dimethylformamide were mixed, and then the temperature was raised to 65° C., and 0.25 g of polyethylene glycol diglycidyl ether was added, and the mixture was stirred at 65° C. for 4 h to finally obtain triethylenetetramine-polyethylene glycol diglycidyl ether; The modified composite material is prepared by the following steps: The composite material and N, N-dimethylformamide are mixed, subjected to ultrasonic treatment for 0.5-1.5 hours, triethylenetetramine-polyethylene glycol diglycidyl ether is added, and stirred at 75-85° C. for 22-24 hours, and then washed with N, N-dimethylformamide and deionized water in sequence, and then vacuum freeze-dried to obtain a modified composite material; The composite material is prepared by the following steps: The graphene oxide is mixed with an ethanol solution, stirred for 0.5-1.5 hours, and then ultrasonically treated for 0.5-1.5 hours to obtain a suspension, and then the alkali-treated glass fiber is immersed in the suspension for 15-20 minutes, and after drying, a mixture is obtained, deionized water and anhydrous ethanol are mixed, KH550 is added and stirred evenly to obtain a KH550 solution, the mixture is mixed with the KH550 solution in a hydrochloric acid solution for 25-35 minutes, filtered, washed with deionized water, and dried at room temperature to finally obtain a composite material.

2. A high heat-resistant glass fiber reinforced ABS material according to claim 1, characterized in that: The usage ratio of the intumescent flame retardant, thionyl chloride and the modified composite material is 0.8-1.2g:40-60mL:0.8-1.2g.

3. The high heat-resistant glass fiber reinforced ABS material according to claim 1, characterized in that: The usage ratio of the composite material and triethylenetetramine-polyethylene glycol diglycidyl ether is 0.1-0.2g:0.05-0.1g.

4. The high heat-resistant glass fiber reinforced ABS material according to claim 1, characterized in that: The usage ratio of graphene oxide, ethanol solution, alkali-treated glass fiber and KH550 is 0.7-0.8 g: 90-110 mL: 4.5-5.5 g: 0.8-1.2 g.

5. A method for preparing the high heat-resistant glass fiber reinforced ABS material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The ABS resin, modified glass fiber, lubricant, antioxidant and silane coupling agent are mixed at room temperature for 5-10 minutes, and after being evenly mixed, they are added into a twin-screw extruder, and extruded into granules after melt blending. The extrusion granulation temperature is 205-230°C, and the screw speed is 240-300r / min, and finally a high heat-resistant glass fiber reinforced ABS material is obtained.

6. The high heat-resistant glass fiber reinforced ABS material according to claim 5, characterized in that: The antioxidant is one or more of pentaerythritol ester, phosphite and n-octadecyl propionate.

7. The high heat-resistant glass fiber reinforced ABS material according to claim 5, characterized in that: The lubricant is polyethylene wax or N,N'-ethylenebisoleamide.

Citation Information

Patent Citations

  • Method for preparing solid aldehyde cloth through two-step method

    CN114016296A

  • Graphene modified epoxy resin-based composite material plate and preparation method thereof

    CN114196166A

Cited By

  • Abs composite plastic for motorcycle cowling and method for manufacturing the same

    CN122790372A